2017
DOI: 10.1590/0103-8478cr20170170
|View full text |Cite
|
Sign up to set email alerts
|

Economic profitability in conventional and irrigated coffee production systems in three municipalities in the Marilia region of São Paulo, Brazil

Abstract: The objective of this study was to evaluate the economic benefit of coffee cultivation, with a focus on the distinction between conventional and irrigated coffee production systems. For the development of the study, the various productive systems were delineated from the data provided by a sample of producers to generate a matrix of average technical coefficients. The methodology used to estimate the operating cost of production is the one used by the Instituto de Economia Agrícola (IEA). Profitability indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…The profitability of passion fruit cultivation is similar to other significant agricultural activities in Brazil, e.g., soybean production with molybdenum application, which achieved profitability indices ranging from 76.80% to 79.65% (OLIVEIRA et al, 2015). However, several agricultural activities have lower profitability than organic passion fruit cultivation, e.g., cowpea, with which Vieira et al (2018) obtained a profitability index of 39.02%, and conventional coffee cultivation (Coffea arabica), which can be influenced by seasonality during the off-season, alternating between negative (-13.9%) and positive profitability indices (44.8%) (TURCO et al, 2017). The revenue obtained with the activity accounts for a total monthly income of R$ 7,129.64 and net revenue of R$ 4,918.18 when using artificial pollination.…”
Section: Resultsmentioning
confidence: 99%
“…The profitability of passion fruit cultivation is similar to other significant agricultural activities in Brazil, e.g., soybean production with molybdenum application, which achieved profitability indices ranging from 76.80% to 79.65% (OLIVEIRA et al, 2015). However, several agricultural activities have lower profitability than organic passion fruit cultivation, e.g., cowpea, with which Vieira et al (2018) obtained a profitability index of 39.02%, and conventional coffee cultivation (Coffea arabica), which can be influenced by seasonality during the off-season, alternating between negative (-13.9%) and positive profitability indices (44.8%) (TURCO et al, 2017). The revenue obtained with the activity accounts for a total monthly income of R$ 7,129.64 and net revenue of R$ 4,918.18 when using artificial pollination.…”
Section: Resultsmentioning
confidence: 99%
“…For producers in Puebla, the BCR was 1.0 and for those in Oaxaca, 0.81 (Table 2). In previous studies, negative profitability was reported for small-scale producers in Hawaii (Woodill et al, 2014) and for producers in Brazil (Turco et al, 2017), while Espinosa-García et al (2016) reported for Mexico that yields under 4.5 tons per hectare generate negative profitability. The producers, once the cherry coffee production has been harvested, have the options of selling the coffee as cherry or processing it (depulping, washing and drying).…”
Section: Costs and Profitability Of Coffee Productionmentioning
confidence: 91%
“…For the economic evaluations, the soybean sale price, inputs purchase price, and other expenses were determined based on the current market values (Turco et al 2017, Gaspar et al 2018. Among the cost system classifications, the following components that are part of the production process were surveyed: inputs [aluminum silicate, trifloxystrobin + prothioconazole (fungicide mixture), seeds of the cultivars used, seed treatment (mixture of pyraclostrobin {25 g L -1 } + thiophanate-methyl {225 g L -1 } + fipronil {250 g L -1 }), biological inoculant, 00-20-20 fertilizer, potassium chloride, and glyphosate] and agricultural mechanization (harrowing, sowing, topdressing fertilization, spraying and harvesting).…”
Section: Methodsmentioning
confidence: 99%